Mobile internet access and the desire to emigrate - Joop Adema; Cevat Giray Aksoy; Panu Poutvaara (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
How does mobile internet access affect the desire to emigrate and migration plans? To answer this question, we combine survey data on more than 600,000 individuals from 110 countries with data on worldwide 3G mobile internet rollout. We show that an increase in mobile internet access increases desire to emigrate. This effect is particularly strong for higher-income individuals in low-income countries. We identify three potential mechanisms. Access to the mobile internet lowers the cost of acquiring information and leads to a drop in perceived material well-being and trust in government. Using municipal-level data from Spain, we also document that 3G rollout increased actual migration flows.
Keywords: F22; 330; migration intentions; desire to emigrate; internet access; 3G internet